Psikopat: Ciri, Penyebab dan Solusinya dalam Islam - Mahdi NK (Jurnal Sosiologi Agama Indonesia (JSAI), 2021)
This article describes psychopaths related to the characteristics, causes, and solutions to overcome them in Islamic teachings. In completing this article, the author uses a qualitative approach, namely by studying literature or reviewing literature related to psychopaths and the teachings of Islam. This study identifies three factors that cause psychopathic behavior: genetic, environmental, and traumatic factors. The solution in Islam is to read the Qur'an, pray at night, hang out with pious people, fast, and remember. These five actions are known as Islamic psychotherapy, which can overcome psychopathic behavior.